2021
DOI: 10.1007/s00289-021-03857-w
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive and smartphone colorimetric assay for the detection of hydrogen peroxide based on antibacterial and antifungal matcha extract silver nanoparticles enriched with polyphenol

Abstract: Current trends in scientific studies focus on the development of smartphone-based biosensors via green nanoparticle for clinical diagnosis, food, and environmental monitoring. In this study, we developed a novel portable smartphone-based biosensor via green dendrimer-coated matcha extract/silver nanoparticles (ME-Ag NPs) enriched with polyphenol for detecting hydrogen peroxide (H 2 O 2 ). Also, we investigated the biological evaluation of the nanostructure as a saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…AgNPs that were enhanced with polyphenols were created using the technique outlined by Tan et al 23 Silver nitrate (AgNO 3 ) was dissolved in 200 mL of deionized water, amounting to 0.32 g. The mixture was then agitated for 10 min at 25°C. In 10 mL of distilled water, 0.016 g of NaOH was dissolved, and the mixture was agitated for 10 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…AgNPs that were enhanced with polyphenols were created using the technique outlined by Tan et al 23 Silver nitrate (AgNO 3 ) was dissolved in 200 mL of deionized water, amounting to 0.32 g. The mixture was then agitated for 10 min at 25°C. In 10 mL of distilled water, 0.016 g of NaOH was dissolved, and the mixture was agitated for 10 min at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…AgNPs that were enhanced with polyphenols were created using the technique outlined by Tan et al 23 Silver nitrate (AgNO 3 ) was dissolved in 200 mL of deionized water, amounting to 0.32 g.…”
Section: Preparation Of Agnps Enriched With Polyphenolmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that the detection of H 2 O 2 using this novel nanosensor is highly selective and rapid. (Tan et al, 2022) (Continues)…”
Section: Data Not Availablementioning
confidence: 99%